The family creative workshop : sculptur seasheels seed sprouting serigraphy sewing without a pattern shadow theater shaker furniture ahelters and tents ship models silhouettes - Bragdon, Allen Davenport (Plenary Publications International, 1976)
128 p. : il.; 27 cm.